(untitled) (PUSA Journal of Hospitality and Applied Sciences, 2025)
Background: This study evaluates the effectiveness and perception of the performance appraisal mechanism from the employees’ perspective. Objective: To evaluate the performance appraisal mechanism and understand its impact on employee motivation, perception and productivity. Methodology: A quantitative survey-based approach was adopted among 100 employees working across hospitality, education, marketing, and IT organizations in Delhi and NCR. Data were collected through a structured questionnaire and analyzed using descriptive statistics. Results: The findings reveal that a majority of employees consider appraisals an important driver of motivation and fairness. Constructive feedback and transparent communication were identified as crucial determinants of satisfaction. Conclusion: The study concludes that fair and well-communicated appraisal systems improve employee engagement, trust and organizational performance.